Religiosity and subjective well-being in the Arab context: addendum and extrapolation - Abdel-Khalek, Ahmed M. (2019)
Three reviewers have reviewed the book Religiosity and Subjective Well-being in the Arab Context. These reviewers have raised specific important points. The present paper aims to address, extend and comment on the main points in their review. As an extension of the research papers in that book, other co-authored studies are summarised. Then, the Arabic and international results on the religiosity-well-being (WB) association are compared. Since the use of the single-item self-rating scales was frequently criticised, the merits of their use in this book was successfully demonstrated. The mechanisms and pathways between religiosity-WB have discussed. Then, future research has suggested. It was concluded that the Arabic studies provide sound evidence to support the positive association between religiosity and both health and WB. Religiosity can help individuals reduce the pain of loss, and it may serve in the prevention and amelioration of disease and intervention for augmenting WB.
Keywords: Arab; Religiosity; Subjective well-being